EVALUASI CAPAIAN PEMBELAJARAN BERBASIS QUALITY CONTROL DALAM MEWUJUDKAN PEMBELAJARAN YANG BERKUALITAS BAGI PESERTA DIDIK - Trimiltin, Ricky; Fuad, Nurhattai; Kamaluddin, Kamaluddin (Jurnal Manajemen Pendidikan, 2024)
This study aims to analyze the evaluation of quality control-based learning outcomes in realizing quality learning for students. In order for monitoring and evaluation to run well, periodic procurement based on quality control is needed, it is intended that educators have the latest data regarding the achievement of learning outcomes on a regular basis so as to improve the quality of learning. The research method used is a descriptive method with a literature approach through literature on evaluating learning outcomes and quality control-based evaluation policies. The answer to the results of this study is the evaluation of quality control-based outcomes is an evaluation carried out by educators to measure the success of the learning process through quality control based on indicators of learning outcomes. In implementing all learning outcomes in order to realize the quality of learning, quality control-based evaluation procurement is needed which aims to assess the achievement of goals, measure various aspects of various lessons, motivate student learning, become an evaluation as a basis for curriculum changes, and determine follow-up assessment results.